Real life experience with atrial fibrillation cryoballoon ablation: results from a nationwide registry. (25th November 2020) - Lubimceva, T; Topchyan, A; Davtyan, K; Artiykhina, E; Tarasiyk, E; Kosonogov, A; Kryzhanovsky, D; Korolev, S; Kolunin, G; Sagitov, I; Nechepurenko, A; Grachev, N; et al.
Abstract: : Cryoballoon ablation (CBA) is an effective strategy for AF management. The Russian Cryoballoon Atrial Fibrillation Ablation Registry (NCT03040037) is a prospective observational multicenter national registry that aims to provide real-world efficacy, safety and outcomes of this technology. Purpose: To evaluate the CBA efficacy, types of adverse events following CBA based on a multicenter nationwide registry. Materials and methods: A web-based registry platform was developed for prospective data entry. The platform consisted of 8 sections: AF ablation experience, patient and CBA characteristics, periprocedural management, 12-month FU, redo procedures, early and late procedure-related complications. Inclusion criteria were the following: indications for AF catheter ablation, planned CBA, a signed informed consent. 32 ablation centers and 1118 patients (572 males, a mean age 68.3±11.4) were included into the registry. Paroxysmal AF was presented in 722 pts, persistent AF – 350 pts, long standing persistent AF – 46 pts. The main underlying diseases were hypertension, coronary artery disease, chronic heart failure; less commonly - hypertrophic cardiomyopathy and dilated cardiomyopathy. The mean LA diameter was 44.7±11.1 mm, LVEF was 62.6±10.8%. The mean BMI was 32.3±3.5 kg/m 2 . Cardioversion prior to CBA was performed in 32.8%. There were different strategies of AF recurrence documentation: ECG, 24-hour ECG monitor, ECG loop recorder implantation. Results: The mean temperature of cryoablation was −45.7±17.4 C. The mean fluoroscopy time was 23.98 mins. The mean patient procedure duration was 108.46 mins [min 30; max 266]. The combination of RFA and CBA was reported in 9 cases. Periprocedural anticoagulant therapy included: uninterrupted NOACs (535 pts), bridge anticoagulation (365 pts), uninterrupted warfarin (67 pts), anticoagulation initiated only after CBA (151 pts). Transesophageal echo-guided CBA was performed in 126 cases, intracardiac echocardiography-guided CBA was performed in 474 cases. Esophageal temperature was controlled in 16 cases. A 12-months follow-up was completed in 906 pts (81.0%). Arrhythmia recurrence was documented in 238 cases (21.3%), mainly AF. Elective cardioversions were performed in 39 pts. Redo ablation procedures were performed in 122 cases. There were a wide range of antithrombotic therapy, as well as pts without anticoagulants despite the fact of AF recurrence. There were 35 (3.1%) CBA-related major adverse events. Esophageal damage was found in 3 cases. There were registered 3 deaths (1 – oncology, and 2 due to unknown cause), 1 MI, 3 persistent phrenic nerve dysfunctions, 3 valve dysfunctions. Conclusion: This nationwide registry represents contemporary safety and efficacy of CBA for AF. A high success rate of the procedure has been shown during 12 months post procedure. Although a total low number of procedure-related complications has been noted, the occurrence of life-threatening adverse events calls for a caution. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Government of the Russian Federation